INTONATIONAL DEVICES IN THE SPEECH PROSODY - Cейдегали, Д.Д. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2020)
Тhis article is committed to the linguistic examination of intonation, its components and capacities within the English language, which is one of the foremost curiously, questionable and vital issues of not only theoretical phonetics, but also of common linguistics of the present time.
Keywords: intonation; speech melody; sentence - stress; the tempo of speech; the process of speech; emotions